Sodium Hydrogen Carbonate Powder Catalyzed Intermolecular Wittig Reaction of Fluorin-Containing Stabilized Phosphorus Ylides with Ninhydrin - RAMAZANI, ALI (Asian Journal of Chemistry, 2010)
Protonation of the highly reactive 1:1 intermediates, produced in the reaction between triphenylphosphine and dialkyl acetylenedicarboxylates, by 2,2,2-trifluoroethanol leads to vinyltriphenylphosphonium salts, which undergo Michael addition reaction with conjugate base to produce the corresponding fluorine-containing stabilized phosphorus ylides. Sodium hydrogen carbonate powder was found to catalyze intermolecular Wittig reaction of the fluorinecontaining stabilized phosphorus ylides with ninhydrin under microwave irradiation (0.5 KW, 3 min) in solvent-free conditions in high conversions.